Suppementation of Kelor Leaf (Moringa oleifera) Aqueous Extract Increase on Post-Thawed Limousin Bull Sperm Quality - Wajdi, Syuhuud Arumbinang; Utomo, Budi; Rimayanti, Rimayanti; Safitri, Erma; Suprayogi, Tri Wahyu; Wurlina, Wurlina (Universitas Airlangga, 2021)
The purpose of this research was to determine the best dosage of Moringa oleifera Aqueous extract in egg yolk skim milk extender for post thawed Limousin Bull sperm quality on aspect viability, and the level of. The treatment was divided into five groups: egg yolk and skim milk diluter (P0), 2,5% M. oleifera aqueous ekstract in 4 ml egg yolk skim milk (P1), 5% M. oleifera aqueous ekstract in 4 ml egg yolk skim milk (P2), 10% M. oleifera aqueous ekstract in 4 ml egg yolk skim milk (P3), 20% M. oleifera aqueous ekstract in 4 ml egg yolk skim milk (P4). The sperm quality was observed post thawing. The data were analyzed using ANOVA and Duncant Test. The best sperm motility showed on P2 with 43b ± 5,70, the best sperm viability showed on P3 with 58,20b ± 8,72 and than the lowest level of malondialdehyde showed on P4 with 5,434a ± 1,034. In conclusion addition of M. oleifera on dose 10% can increase quality of Limousin Sperm Post Thawed.